The Role of Hypertonic Saline in the Management of Acute Traumatic Spinal Cord Injury: A Narrative Review of the Literature - Nadeem, Syed Faisal; Hassan, Ahmad; Tahir, Tabinda; Carelli, Luis E.; Rubiano, Andres M.; Khan, Ahsan Ali (Asian Journal of Neurosurgery, 2025)
Traumatic spinal cord injury (TSCI) is a prevalent condition associated with high morbidity and mortality. The pathophysiology of TSCI involves primary injury from the traumatic insult itself and secondary injury (SI) from maladaptive biological processes that serve to aggravate the original insult, such as edema and inflammation, which exacerbate the primary injury and prevent healing and recovery. Research is currently underway to derive therapies to reduce SI-mediated damage. Hypertonic saline (HTS) has emerged as one such therapy. We conducted a literature search for animal and human studies investigating the role of HTS in TSCI on PubMed. Murine studies have shown it to possess antiedema, anti-inflammatory, and vasodilatory properties, which aid in reducing SI and thus improving functional outcomes. Combining HTS with other drugs such as procoagulants, methylprednisolone, and nitroprusside has also been shown to possess greater therapeutic benefit in rodent models of TSCI compared with single therapy with HTS. No human studies have been done till now to assess the benefits of HTS in improving human TSCI outcomes. Future research must focus on determining specific dosing and frequency regimens for HTS in human TSCI patients and on elucidating the extent of benefit it provides to them in improving their outcomes.
Keywords: hypertonic; traumatic; spine; injury; outcome